Valorization of water hyacinth through supercritical CO2 extraction of stigmasterol - de Melo, Marcelo M. R.
Water hyacinth (Eichornia crassipes) is an invasive aquatic plant that has recently been showed to have a remarkable abundance of stigmasterol in leaves and stalks. The supercritical fluid extraction (SFE) of E. crassipes parts was performed for the first time in this work, covering total yield (eta(total)), stigmasterol yield (eta(stig)), and its concentration in extracts (c(stig)). Several experiments were performed at 200 bar, two temperatures (40 and 60 degrees C), and three cosolvent amounts (0, 5, 10 wt.% ethanol). Moreover, two cumulative extraction curves were measured (200 bar and 40 or 60 degrees C). The results showed that eta(total) ranged from 0.64 to 0.73 wt.% after 6 h of extraction, eventually reaching 1.88 wt.% if the extraction time four times and ethanol is included. For eta(stig), 6 h of SFE yielded 0.20-0.22 wt.% with no noticeable advantage in extending the run time and/or adding ethanol. In comparison to Soxhlet results, the performance of SFE in both eta(total) and eta(stig) fell below dichloromethane results. Nonetheless, when stigmasterol concentration was analyzed, a significant selectivity gain was observed on SFE, which originated extracts up to 3:1 richer in stigmasterol. This was also confirmed after estimating practical stigmasterol selectivities, whose values attained 1.14 at 200 bar and 40 degrees C, while at 60 degrees C they reached ca. 0.90 at most. Modeling suggested intraparticle diffusion as the apparently dominant mass transport mechanism of the process. In the whole, the results encourage the valorization of E. crassipes through a green technology such as SFE. (C) 2015 Elsevier B.V. All rights reserved.